Question

Nested Form of a Polynomial Expand Q to prove that the polynomials P and Q are the same P(x)=3x^{4}-5x^{3}+x^{2}-3x+5 Q(x)=(((3x-5)x+1)x-3)x+5. Try to evalue P(2) and Q(2) in your head, using the forms given.

Polynomial arithmetic
ANSWERED
asked 2021-07-29
Nested Form of a Polynomial Expand Q to prove that the polynomials P and Q are the same.
\(\displaystyle{P}{\left({x}\right)}={3}{x}^{{{4}}}-{5}{x}^{{{3}}}+{x}^{{{2}}}-{3}{x}+{5}\)
\(\displaystyle{Q}{\left({x}\right)}={\left({\left({\left({3}{x}-{5}\right)}{x}+{1}\right)}{x}-{3}\right)}{x}+{5}\)
Try to evalue P(2) and Q(2) in your head, using the forms given. Which is easier? Now write the polinomial \(\displaystyle{R}{\left({x}\right)}={x}^{{{5}}}-{2}{x}^{{{4}}}+{3}{x}^{{{3}}}-{2}{x}^{{{2}}}+{3}{x}+{4}\) in "nested" form, like the polinomial Q. Use the nested form to find R(3) in your head.

Expert Answers (1)

2021-07-30
Q(2) can be easily calculated (mentally) than P(2) since in each step we have to perform linear operations starting from the inside.
While evaluating P(2) mentally we find that larger number occurs in every step.
To find P(2):
\(\displaystyle{P}{\left({x}\right)}={3}{x}^{{{4}}}-{5}{x}^{{{3}{\mid}+{x}^{{{2}}}-{3}{x}+{5}}}\)
\(\displaystyle{P}{\left({2}\right)}={3}{\left({2}\right)}^{{{4}}}-{5}{\left({2}\right)}^{{{3}}}+{\left({2}\right)}^{{{2}}}-{3}{\left({2}\right)}+{5}\)
\(\displaystyle={3}{\left({16}\right)}-{5}{\left({8}\right)}+{4}-{6}+{5}\)
\(\displaystyle={48}-{40}+{4}-{6}+{5}\)
\(\displaystyle={57}-{46}\)
\(\displaystyle={11}\)
To find Q(2):
\(\displaystyle{Q}{\left({x}\right)}={\left({\left({\left({3}{x}-{5}\right)}{x}+{1}\right)}{x}-{3}\right)}{x}+{5}\)
\(\displaystyle{Q}{\left({2}\right)}={\left({\left({\left({3}{\left({2}\right)}-{5}\right)}{2}+{1}\right)}{2}-{3}\right)}{2}+{5}\)
\(\displaystyle={\left({\left({\left({1}\right)}{2}+{1}\right)}{2}-{3}\right)}{2}+{5}\)
\(\displaystyle={\left({\left({3}\right)}{2}-{3}\right)}{2}+{5}\)
\(\displaystyle={\left({6}-{3}\right)}{2}+{5}\)
\(\displaystyle={3}{\left({2}\right)}+{5}\)
\(\displaystyle={6}+{5}\)
\(\displaystyle={11}\)
Now we have to write R(x) in nested form.
\(\displaystyle{R}{\left({x}\right)}={x}^{{{5}}}-{2}{x}^{{{4}}}+{3}{x}^{{{3}}}-{2}{x}^{{{2}}}+{3}{x}+{4}\)
Now we have factor out x.
\(\displaystyle{R}{\left({x}\right)}={\left({x}^{{{4}}}-{2}{x}^{{{3}}}+{3}{x}^{{{2}}}-{2}{x}+{3}\right)}{x}+{4}\)
\(\displaystyle={\left({\left({x}^{{{3}}}-{2}{x}^{{{2}}}+{3}{x}-{2}\right)}{x}+{3}\right)}{x}+{4}\)
\(\displaystyle={\left({\left({\left({x}^{{{2}}}-{2}{x}+{3}\right)}{x}-{2}\right)}{x}+{3}\right)}{x}+{4}\)
\(\displaystyle={\left({\left({\left({\left({x}-{2}\right)}{x}+{3}\right)}{x}-{2}\right)}{x}+{3}\right)}{x}+{4}\)
We can calculate R(3) mentally.
\(\displaystyle{R}{\left({x}\right)}={\left({\left({\left({\left({x}-{2}\right)}{x}+{3}\right)}{x}-{2}\right)}{x}+{3}\right)}{x}+{4}\)
\(\displaystyle{R}{\left({3}\right)}={\left({\left({\left({\left({3}-{2}\right)}{3}+{3}\right)}{3}-{2}\right)}{3}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({\left({\left({\left({1}\right)}{3}+{3}\right)}{3}-{2}\right)}{3}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({\left({\left({6}\right)}{3}-{2}\right)}{3}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({\left({18}-{2}\right)}{3}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({\left({16}\right)}{3}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({48}+{3}\right)}{3}+{4}\)
\(\displaystyle={\left({51}\right)}{3}+{4}\)
\(\displaystyle={153}+{4}\)
\(\displaystyle={157}\)
\(\displaystyle{R}{\left({3}\right)}={157}\)
The polynomials P and Q are the same by expanding Q is proved.
6
 
Best answer

expert advice

Have a similar question?
We can deal with it in 3 hours

Relevant Questions

asked 2021-02-21

DISCOVER: Nested Form of a Polynomial Expand Q to prove that the polynomials P and Q ae the same \(P(x) = 3x^{4} - 5x^{3} + x^{2} - 3x +5\)
\(Q(x) = (((3x - 5)x + 1)x^3)x + 5\)
Try to evaluate P(2) and Q(2) in your head, using the forms given. Which is easier? Now write the polynomial
\(R(x) =x^{5} - 2x^{4} + 3x^{3} - 2x^{2} + 3x + 4\) in “nested” form, like the polynomial Q. Use the nested form to find R(3) in your head.
Do you see how calculating with the nested form follows the same arithmetic steps as calculating the value ofa polynomial using synthetic division?

asked 2021-02-08

Nested Form of a Polynomial Expand Q to prove that the polynomials P and Q ae the same \(\displaystyle{P}{\left({x}\right)}={3}{x}^{{4}}-{5}{x}^{{3}}+{x}^{{2}}-{3}{x}+{5}\ {Q}{\left({x}\right)}={\left({\left({\left({3}{x}-{5}\right)}{x}+{1}\right)}{x}-{3}\right)}{x}+{5}\) Try to evaluate P(2) and Q(2) in your head, using the forms given. Which is easier? Now write the polynomial \(\displaystyle{R}{\left({x}\right)}={x}^{{5}}—{2}{x}^{{4}}+{3}{x}^{{3}}—{2}{x}^{{3}}+{3}{x}+{4}\) in “nested” form, like the polynomial Q. Use the nested form to find R(3) in your head. Do you see how calculating with the nested form follows the same arithmetic steps as calculating the value ofa polynomial using synthetic division?

asked 2021-08-12
Find all the real zeros of the polynomial.
\(\displaystyle{P}{\left({x}\right)}={3}{x}^{{{3}}}+{5}{x}^{{{2}}}-{2}{x}-{4}\)
asked 2021-08-08
Consider the polynomial \(\displaystyle{2}{x}^{{{3}}}-{3}{x}^{{{2}}}+{x}^{{{5}}}\). Which of the following statements about the polynomial are not correct?
A. The standard form of the polynomial is \(\displaystyle{x}^{{{5}}}+{2}{x}^{{{3}}}-{3}{x}^{{{2}}}\).
B. The polynomial is a trinomial.
C. The polynomial is quintic.
D. The polynomial has a linear term.
...